Analysis Of Learning Math Based (HOTS) Through Problem Based Learning Model In Class V SD - Rizky, Putry Aliefhya; Syam, Nur; Rahmawati, Rahmawati (ALENA : Journal of Elementary Education, 2025)
This study aims to determine (1) the implementation of higher order thinking skill (HOTS) based mathematics learning through problem based learning model in class V SD Negeri Kapasa, (2) the level of effectiveness of problem based learning (PBL) model on HOTS based mathematics learning, (3) factors that hinder HOTS based mathematics learning through problem based learning (PBL) model. This research uses a qualitative approach, with a descriptive qualitative research type. The objects in this research are students and fifth grade teachers of SD Negeri Kapasa. In this study, the data collection techniques used were observation, tests, interviews and documentation. The implementation of HOTS-based mathematics learning through the PBL model makes students think systematically, able to analyze problems from various aspects, train creative and innovative thinking levels and make students more confident. Factors that can hinder HOTS-based mathematics learning through the PBL model are the lack of time allocation in applying the model and the different grasping power of students so that the solution that can be done by the teacher is able to manage the time allocation properly as well as the seating arrangement of students, give additional assignments to students and provide additional tutoring to students who are lacking in mathematics subjects.